2016
DOI: 10.1016/j.apjtm.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential, tannin and polyphenol contents of seed and pericarp of three Coffea species

Abstract: The obtained data highlight the potential role of C. benghalensis as a new source of natural antioxidants and polyphenols compared to C. arabica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
3
23
0
1
Order By: Relevance
“…This is probably due to the BHT, vitamin C and vitamin E having the nature of being the established antioxidants, thus having higher ability to donate electron than the spent coffee samples. Plus, according to the previous study, although C. liberica is less used commercially, the antioxidant effect of its green seeds is comparable to that of C. arabica and C. robusta (Patay et al, 2016). Figure 2(B) exhibits the results from FTC method of different SCG extract on the 6 th day of incubation.…”
Section: Dpph Radical Scavenging Assaysupporting
confidence: 52%
“…This is probably due to the BHT, vitamin C and vitamin E having the nature of being the established antioxidants, thus having higher ability to donate electron than the spent coffee samples. Plus, according to the previous study, although C. liberica is less used commercially, the antioxidant effect of its green seeds is comparable to that of C. arabica and C. robusta (Patay et al, 2016). Figure 2(B) exhibits the results from FTC method of different SCG extract on the 6 th day of incubation.…”
Section: Dpph Radical Scavenging Assaysupporting
confidence: 52%
“…In one of our previous study, a high phenolic content was observed in the immature pericarp of C. benghalensis and C. liberica compared with that of C. arabica. In addition, the immature pericarp of Bengal coffee and the immature seed of Arabic coffee showed a significant polyphenol content too [29]. Other phytochemical studies showed that the total hydroxycinnamic acid content of C. arabica was significantly higher than that of Coffea sessiliflora Bridson, Coffea resinora Hook.f., and Coffea leroyi A.P.Davis.…”
Section: Phytochemical Features Of Coffea Arabica Lmentioning
confidence: 96%
“…Sedangkan E.coli merupakan bakteri yang menyebabkan penyaki diare dan iritasi luka pada kulit. E.coli merupakan kelompok bakteri gram negatif yang berbentuk batang pendek dan panjangnya sekitar 2 μm, diameter 0,7 μm, lebar 0,4-0,7μm (va Brigitta Patay et al 2016). E. coli umumnya hidup dalam saluran pencernaan manusia dan dapat menyebabkan penyakit disentri.…”
Section: Abstrak: Aktivitas Daya Hambat Limbah Daging Buah Kopi Robusunclassified